2017
DOI: 10.3727/096504016x14759554689565
|View full text |Cite
|
Sign up to set email alerts
|

[ARTICLE WITHDRAWN] Upregulation of MicroRNA-935 Promotes the Malignant Behaviors of Pancreatic Carcinoma PANC-1 Cells via Targeting Inositol Polyphosphate 4-Phosphatase Type I Gene (INPP4A)

Abstract: Our goal was to determine the roles and regulatory mechanism of microRNA-935 (miR-935) in the progression of pancreatic cancer. The results showed that, compared with normal pancreatic tissues and cells, the expression of miR-935 was markedly upregulated, while INPP4A expression was obviously downregulated in pancreatic cancer tissues and PANC-1 cells. After transfection with the miR-935 inhibitor, miR-935 was significantly suppressed, and suppression of miR-935 significantly inhibited cell proliferation, supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…31 As for miR-935, Wang et al found that miR-935 was upregulated in pancreatic carcinoma and targeted inositol polyphosphate 4-phosphatase type I to promote cancer malignant behavior. 18 Liu et al confirmed the truth that miR-935 could target SOX7 to promote liver cancer cell proliferation and migration. 19 Yang et al informed that miR-935 promoted cell proliferation by targeting SOX7 in gastric cancer.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…31 As for miR-935, Wang et al found that miR-935 was upregulated in pancreatic carcinoma and targeted inositol polyphosphate 4-phosphatase type I to promote cancer malignant behavior. 18 Liu et al confirmed the truth that miR-935 could target SOX7 to promote liver cancer cell proliferation and migration. 19 Yang et al informed that miR-935 promoted cell proliferation by targeting SOX7 in gastric cancer.…”
Section: Discussionmentioning
confidence: 90%
“…15 Mature miRNA regulates gene expression negatively by repressing the translation of the target gene's proteins from messenger RNAs (mRNAs) or by binding to the 3ʹ-untranslated regions to increase the degradation of mRNAs. 16,17 Recently, miR-935 is observed to be upregulated in pancreatic cancer, 18 liver cancer 19 and gastric cancer. 20 However, the expression and potential roles of miR-935 in renal cancer progression are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [31] showed that overexpression of miR-15b induced EMT by inhibiting SMURF2 in the pancreatic cancer cell line BxPC-3. Moreover, Wang et al showed that upregulation of miR-935 promoted EMT by inhibiting inositol polyphosphate 4-phosphatase type I gene in the pancreatic cancer cell line HPDE6-C7 [32]. However, these studies focused only on miR-15b and miR-935, respectively, and did not examine miRNA profiles in pancreatic cancer tissues or pancreatic cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…As a novel miRNA, the studies on miR-935 are not very abundant. miR-935 has been reported to be a prognostic biomarker of weight loss (10); furthermore, miR-935 has also been reported to be upregulated in cluster of differentiation133+ neural stem cells when compared with medulloblastoma specimens (11); in addition, upregulation of miR-935 promotes the malignant behaviors of PANC-1 pancreatic carcinoma cells through targeting inositol polyphosphate 4-phosphatase type I gene (12). However, its specific role and target gene in NSCLC have not been reported.…”
Section: Introductionmentioning
confidence: 99%